Extremely reduced dielectric confinement in two-dimensional hybrid perovskites with large polar organics. Issue 1 (December 2018) - Cheng, Bin; Li, Ting-You; Maity, Partha; Wei, Pai-Chun; Nordlund, Dennis; Ho, Kang-Ting; Lien, Der-Hsien; Lin, Chun-Ho; Liang, Ru-Ze; Miao, Xiaohe; Ajia, Idris; Yin, Jun; et al.
Abstract Two dimensional inorganic–organic hybrid perovskites (2D perovskites) suffer from not only quantum confinement, but also dielectric confinement, hindering their application perspective in devices involving the conversion of an optical input into current. In this report, we theoretically predict that an extremely low exciton binding energy can be achieved in 2D perovskites by using high dielectric-constant organic components. We demonstrate that in (HOCH2 CH2 NH3 )2 PbI4, whose organic material has a high dielectric constant of 37, the dielectric confinement is largely reduced, and the exciton binding energy is 20-times smaller than that in conventional 2D perovskites. As a result, the photo-induced excitons can be thermally dissociated efficiently at room temperature, as clearly indicated from femtosecond transient absorption measurements. In addition, the mobility is largely improved due to the strong screening effect on charge impurities. Such low dielectric-confined 2D perovskites show excellent carrier extraction efficiency, and outstanding humidity resistance compared to conventional 2D perovskites. Two-dimensional inorganic–organic hybrid perovskites are expected to play an important role in photovoltaic devices but suffer from issues related to dielectric confinement. The authors theoretically outline a method and experimentally succeed to overcome this issue by using materials with large dielectric constants.